Pengaruh Motivasi Kerja, Pelatihan Dan Kecerdasan Emosional Terhadap Kinerja Pegawai (Studi Pada Puskesmas Dinoyo Kota Malang) - Raudatul Jannah; Abdul Kodir Djaelani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of work motivation, training and emotional intelligence on employee performance at the Dinoyo Health Center in Malang City. Sampling in this study used saturated sampling, namely by using the entire existing population to be used as a sample. The data analysis method used in this study is the data instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test (Adjusted R2). Based on the results of the research on the multiple linear regression analysis test it is known that work motivation, training and emotional intelligence have a positive effect and on the results of the f test it is known that work motivation, training and emotional intelligence simultaneously have a significant effect on the performance of employees of the Dinoyo Health Center in Malang City. However, in the t test it is known that training has a positive and significant effect on employee performance while work motivation and emotional intelligence have a positive but not significant effect. Keywords : Work Motivation, Training, Emotional Intelligence, Employee Performance